Potential of engineered biomedia for the innovative purification of contaminated river water - Sidek L.; Mohiyaden H.A.; Lee L.K.; Foo K.Y. (Desalination Publications, 2023)
adsorption; biofilm; bioreactor; purification; river water; water quality; water treatment